Forest typological structure of oak forests of volyn height - Novak, A.A.; Kopiy, S.L.; Fizyk, I.V. (Forestry, Forest, Paper and Woodworking Industry, 2018)
Oak (Quercus robur L.) is one of the most common and valuable tree species in the Western Forest-Steppe of Ukraine. Much of the oak forests of the Western Forest-Steppe are concentrated in the forest district of Volyn Upland, which, despite belonging to the Western Ukrainian Forest-Steppe Forest District, is characterized by special geomorphological and climatic conditions, which contributed to the formation of valuable usually mixed oak stands,and also linden, maple, ash. The peculiarities of oak stands distribution in the northern part of the Western Forest-Steppe of Ukraine are analysed in the work. The analysis of forest typological structure of stands with the participation of oak (Quercus robur L.) in the forestry district of Volyn Upland is carried out. The structure of areas and reserves of oak stands in the context of edatopes and forest types has been studied. The average stock per unit area of oak stands of the Volyn Upland is calculated and a comparative characteristic of its ratio with the reserves of oak stands of the Volyn Upland in different types of forest vegetation conditions is made. Based on this analysis, conclusions are made on the productivity and use of edaphic conditions by oak forests in the Volyn Upland. The largest share of oak stands in the Volyn Upland is concentrated in hail conditions – 70,9%. Soil types of forest vegetation conditions make up 23,1% of the area of oak stands. According to the degree of soil moisture, Quercus robur L., in the Volyn Upland, prefers fresh conditions, where 70,6% of oak forests in the region are concentrated. In general, oak (Quercus robur L.) in the study region is involved in the formation of 13 forest types, of which 7 act as a typical species.